Monetary neutrality (1996)
The work for which I have received this prize was part of an effort to understand how changes in the conduct of monetary policy can influence inflation, employment, and production. So much thought has been devoted to this question and so much evidence is available that one might reasonably assume that it had been solved long ago. But this is not the case: It had not been solved in the 1970s when I began my work on it, and even now this question has not been given anything like a fully satisfactory answer. In this lecture I will try to clarify what it is about the problem of bringing available evidence to bear on the assessment of different monetary policies that makes it so difficult, and to review the progress that has been made toward solving it in the last two decades.